IMPLANT THREE-PIECE INFLATABLE PENILE PROTHESIS TO TREAT SEVERE ERECTILE DYSFUNCTION FOLLOWING COMPLEX PELVIC FRACTURE: A CASE REPORT (Vietnam Journal of Community Medicine, 2022)
Pelvic fracture is one of common causes of erectile dysfunction. Penile prothesis implantationis presented to these cases that poorly respond to other standard treatments. This reporteda case of 33-year-old men with severe erectile dysfunction and urethral stricture followingcomplex pelvic fracture due to a traffic accidents were successfully implanted three-pieceinflatable penile prothesis at People’s hospital 115. At the third month of follow-up, thisdevice has been worked effectively, patient could have ability to attain full erection forsexual intercourse. Both patient and partner are satisfied with their sexual lives.
Keywords: Penlie prothesis implantation, erectile dysfunction, pelvic fracture.